The economic importance of Sirnak asphaltites in the next decade - Öcal, Fatih Mehmet; Darıcı, Bülent; Okyar, Mete Cüneyt (SILA SCIENCE, 2012)
What is discussed in this study is that, improvement of the investment enviroment of asphaltite mine, in Turkey's Sirnak province and increasing the competitiveness with the world; mainly within the scope of field studies which was performed by The Mineral Research and Exploration Institute (MRE) in 1930s. Thanks to these findings Turkey Coal Enterprises (TCE) began operating the asphaltite facilities, in and around the province of Sirnak in the late 1970s. Although the managership of these plants are operated by the private sector in the way of royalty after 2002, the research offers a wealth of information about the socio-economic status of the owners of the firms. In tihs study, the difficulties had by the owners of the firms operating the production of asphlaltite in the province of Sirnak, in the process of production, are adressed; beside these difficulties, the correlation between the amount of reserves, legal structure and the employment are analyzed. The research is focused on cross-relations about the asphaltite in the province of Sirnak. By using ANOVA and multiple comparisons, tried to determine the potential for increasing the competitiveness of the province of Sirnak. Despite the wide potential, it can be said that; the managership activities' that operated on the asphaltite mine in the last ten years, could not be enough for the changing the mindset of the new investment structure in province of Sirnak and its image radically.
Keywords: Mining sector; Coal mines; Asphaltite; Investment image; ANOVA test